Real‐Time and Image‐Based AQI Estimation Based on Deep Learning. Issue 6 (8th March 2022) - Zhang, Qiang; Tian, Lifeng; Fu, Fengchen; Wu, Huanyu; Wei, Wei; Liu, Xueyan
Abstract: The real‐time information on surrounding air quality index (AQI) is important for the public to protect themselves from air pollution. Traditional methods have some shortages regarding the estimation time and running efficiency. Consequently, the AQI results cannot meet the needs of personal protection and environmental management. With the popularity of smart terminals, it is easier to collect particular environmental images for AQI estimation tasks. Therefore, a real‐time and image‐based deep learning model named YOLO‐AQI is proposed. Based on the object detection algorithms, the model has better performance regarding the AQI estimation speed. By optimizing the parameter transfer and network structure, the model takes an average of 0.0582 s to perform feature analysis and achieves 75.15% accuracy on AQI estimation tasks. Comparing YOLO‐AQI with several image recognition models (VGG, AlexNet, GoogLeNet, MobileNet, and ResNet), it shows that YOLO‐AQI outperforms other models by 14.8% on accuracy and by 71.1% on running speed. This method can provide real‐time AQI level information for remote areas such as rural. Abstract : A real‐time AQI estimation model based on deep learning and object detection network is proposed. Through the optimization of the neural network structure, the constructed Yolo‐AQI model has advantages in detection accuracy and detection speed. The model has a great effect on environmental management in remote areas.